Interactive effects of canopy-driven changes in light, scour and water flow on microscopic recruits in kelp. (October 2021) - Tatsumi, Masayuki; Layton, Cayne; Cameron, Matthew J.; Shelamoff, Victor; Johnson, Craig R.; Wright, Jeffrey T.
Abstract: Ecosystem engineering kelp forms habitat and influences associated communities by altering abiotic conditions. These conditions can also affect the engineer's own demographic rates but the mechanisms underpinning these feedbacks are not well known. Here, we tested the interactive effects of three abiotic factors engineered by the Australasian kelp Ecklonia radiata (light, water flow and scour) on the early survivorship and growth of its outplanted microscopic recruits. After six weeks, recruit survivorship was high in the absence of scour and low light (2–3 times higher than when scour was present) and under low water flow-ambient light conditions. Growth of sporophytes was strongly related to light, with recruits under ambient light approximately four times larger after six weeks. Overall, reduced scour (for survivorship) and ambient light (for growth) appear crucial for maximising E. radiata recruitment suggesting a healthy forest can provide microenvironments to enhance survivorship while gaps in the canopy enhance growth. Highlight: The ecosystem engineering effects of a kelp canopy on recruitment was investigated. Highest survivorship of recruits occurs when scour is absent, and light is low. Full light is most beneficial for growth of recruits. Intact canopies provide a microenvironment that supports survivorship while gaps enhance growth.